The impact of Language of Learning and Teaching on the performance of commercial subjects in South African rural schools - Mathiba, Thema Adolph; Mamabolo, Joel; Ndlovu, Simon Mfula; Themane, Mahlapahlapana (Frontiers in Education, 2026)
The underperformance and declining enrolment in commercial subjects (Business studies, Economics, and Accounting) in some South African schools in the Capricorn South District have raised concerns about their sustainability. Limited research has explored the role of Language of Learning and Teaching (LOLT) in shaping commercial learners’ performance, particularly in rural schools, despite evidence that poor proficiency in the LOLT can hinder comprehension and curriculum delivery in English-medium subjects. This study examines the effects of LOLT on academic performance in commercial subjects within rural schools in the Capricorn South District. Adopting an interpretive paradigm and qualitative methodology, a multiple case study design was employed. Ten commercial departmental heads from ten secondary schools were purposively sampled. Data was collected through semi-structured interviews with document analysis used to triangulate the findings, then analysed using thematic content analysis. The study found poor proficiency in the LOLT is a barrier to the delivery of the curriculum in commercial subjects. Accordingly, the study concludes that LOLT proficiency is a critical determinant of academic success in commercial subjects. Addressing language barriers through systematic educational reforms, such as teacher training programmes and bilingual education models could improve learners’ outcomes and prevent further decline in subject enrolment.